2014
DOI: 10.1002/art.38307
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Factor as a Potentiator of Anti–Citrullinated Protein Antibody–Mediated Inflammation in Rheumatoid Arthritis

Abstract: Objectives The co-occurrence of rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) is well described in rheumatoid arthritis (RA). However, the mechanisms underlying the potential interaction between these two distinct autoantibodies has not been well defined. We sought to evaluate the epidemiologic and molecular interaction of ACPA and RF with both disease activity as well as measures of RA-associated inflammation. Methods In a cohort of 1,488 Veterans with RA, measures of disease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
126
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 33 publications
14
126
1
4
Order By: Relevance
“…However, this is the first study, to our knowledge, to demonstrate meaningful differences in RF concentration between current and former cigarette smokers as manifested by a corresponding reduced level of disease activity. Thus, the correlation of RF titre with smoking status suggests it to be a potential driver of autoantibody-mediated inflammation and supports recent work by our group and others demonstrating the capacity for RF to potentiate the inflammatory capacity of ACPA immune complexes [26,27].…”
Section: Fig 1 Differential Associations Of Serum Cytokines Acpas Asupporting
confidence: 86%
“…However, this is the first study, to our knowledge, to demonstrate meaningful differences in RF concentration between current and former cigarette smokers as manifested by a corresponding reduced level of disease activity. Thus, the correlation of RF titre with smoking status suggests it to be a potential driver of autoantibody-mediated inflammation and supports recent work by our group and others demonstrating the capacity for RF to potentiate the inflammatory capacity of ACPA immune complexes [26,27].…”
Section: Fig 1 Differential Associations Of Serum Cytokines Acpas Asupporting
confidence: 86%
“…Following B cell repopulation, RF levels rise again and this rise can predict relapse of clinical symptoms [5,12]. Similar to findings in rheumatoid arthritis (RA), combined presence of RF and disease-specific autoantibodies (anti-SS-A/Ro, anti-SS-B/La) may result in higher disease activity in pSS as well [13]. The mechanism behind this synergistic effect is unknown, but crosslinking and/or stabilization of immune complexes, consisting of autoantigens and autoantibodies, by RF is likely involved.…”
Section: Introductionmentioning
confidence: 61%
“…Of note, the concordant presence of IgM RF and ACPA, which occurs in a very large majority of patients, was very recently reported to associate with increased disease activity (69). Even more recently, it was reported that an increase in RF titer enhanced the size and number of erosions in ACPA + but not ACPA 2 patients (70).…”
Section: Discussionmentioning
confidence: 90%